Twin Middle Cerebral Artery with Aneurysm: A Variant of Early Bifurcation or a Discrete Entity - Sahoo, Sushant (J Neurosci Rural Pract, 2017)
The middle cerebral artery (MCA) usually bifurcates into a superior or frontal and inferior or temporal branch. However, it may have various branching pattern, and there may be additional arteries from the anterior circulation supplying its territory. The majority of them remain asymptomatic. Some cases may have aneurismal dilatation due to turbulent blood flow or the weak arterial wall. The surgical approach in these cases may be challenging due to complex anatomical pattern of MCA. In this report, we have described a distinct pattern of left MCA with an aneurysm which was not clear in computed tomography angiogram and further confirmed on digital subtraction angiography. The different anatomical patterns of MCA and their surgical implications have also been discussed.